Impacto of IPSIS-High School on professional choice (Research, Society and Development, 2021)
The Institutional Program for Scientific Initiation Scholarships for High Schools (IPSIS-HS) aims to awaken the scientific vocation and discover new talents. This program has been discussed by authors from different points of view, and this cross-sectional study seeks to qualitatively and quantitatively analyze the impact of the program on the professional choice of participants, relating their participation in it and the choice of training in the area of Biological Sciences and of Health, identifying the level and current characteristics of training of these former students and the relationship of experience with higher education, developed in the Morphophysiology laboratory applied to health at the University of the State of Pará (USPA) in 2011. It was carried out an exploratory field research, then 15 former students were interviewed through a Google Form questionnaire, with open and closed questions. The analysis of descriptive statistics obtained from the data organized in Excel revealed that most individuals had low income, attained higher education in public educational institutions and pursued a career in the area of Biological and Health Sciences. Regarding the qualitative analysis, most participants allege the program's relevant importance for their professional choices and personal growth. In this sense, the work confirms the merit of Programs such as IPSIS-HS and reinforces the need for more investments for the continuity of this important Program.